Ag/NiO nanocomposites derived from alpha-nickel hydroxide for the detection of microbial volatile organic compounds - Vioto, Gabriel Camilo Negrini (2021)
Microorganisms are widely studied due to the risks they can cause in human activities. It can damage the economy and health fields, causing infectious diseases or even the deterioration of food. Thus, there is a need for the control and identification of these organisms. An essential characteristic of microorganisms, in general, is that they produce specific profiles of microbial volatile organic compounds (mVOC) in their cellular metabolism, which can be correlated with infectious diseases or even particular microorganisms. In this work, α-nickel hydroxide (α-Ni(OH)2) and silver (Ag) were used as a precursor of nickel oxide (NiO) and for decorating NiO with different amounts of % mass, respectively. They aim to obtain materials (NiO and Ag/NiO) with pores and silver in their structures. The modifications can guarantee better performance in applying the material both as a sensor for mVOCs and VOCs, through sensitization reactions, caused by the presence of Ag. For selectivity of the samples, acetone, ethanol, 2-butanone, 3-methyl-1-butanol, 2-nonanone, and m-xylene were used; a better selectivity was obtained for 3-methyl-1-butanol, a mVOC. In addition, sensitivity tests were performed, using different concentrations of 3-methyl-1-butanol in a range of 2 to 200 ppm and a test to obtain the optimum operating temperature of the materials.